PERAN MEDIA SOSIAL PADA KEPUTUSAN BERKUNJUNG WISATAWAN KE KOTA BOGOR - Yuviani Kusumawardhani; Wahyu Hidayat (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2020)
Social media is a necessity for everyone because of its usefulness and has an impact on life both to socialize and to boost the economy. This is an opportunity for the tourism sector to promote tourist destinations with a wide market tourist segmentation. Consumers or tourists perceive social media as a more reliable source of information about the promotion of products or services. However, the majority of stakeholders related to tourist destinations in Indonesia have not optimized the use of social media as a promotion. This is the purpose of this study to analyze the role of social media in the decision to visit tourists to Bogor City. This research method is use a quantitative approach with simple linear regression analysis tools. The results showed that social media had a role in the decision to visit tourists to Bogor City but that role was not significant. This happens because, the lack of tourism destination promotion that not optimize to use social media. This research can be used as input for related stakeholders to create content and events that attract tourists to Bogor. In addition, optimizing the use of social media can be done by advertising on social media itself such as Google Ads, Instagram Ads, Youtube Ads and Facebook Ads so that people who initially do not know are not even interested in visiting Bogor, but with this, brand awareness promotion technique they can stimulated tourist to seek further information which ultimately decided to visit the city of Bogor.